HABITUAL LEVEL OF PHYSICAL ACTIVITY AND ASSOCIATED FACTORS IN PATIENTS WITH DIABETES AND HYPERTENSION, USERS OF A FAMILY HEALTH STRATEGY IN TORRES / RS (Fiep Bulletin - online, 2012)
This study aimed to assess the level of habitual physical activity and associated factors in patients with diabetes and hypertension, users of a Family Health Strategy (FHS) of the Municipality of Torres, RS. The sample consisted of 116 individuals, 77 (66.4%) women and 39 (33.6%) men with a mean age of 61.37±10.19 years. For data collection, descriptive exploratory questionnaires were used, one for anthropometric indicators Body Mass Index (BMI), waist circumference (WC), waist hip ratio (WHR) and the International Physical Activity Questionnaire (IPAQ) N°8 long version. We identified 99 patients who had BMI?25.0 kg/m2. AC was favorable to 71 women and unfavorable to 38 men. Regarding WHR values, 50 women and 32 men showed values ? 88.0. With respect to the usual level of physical activity, we found that the subjects were most often classified as sedentary in different fields like in recreation, sport, exercise and leisure PA where women showed (63.7±197.9 min/week) and men showed (57.8±104.99 min/week). We conclude that, while undergoing treatment at an FHS, the subjects have high potential to be victims of cardiovascular events, especially modular factors that must be handled correctly, considering the individual, social and economic aspects of the target population.
Keywords: Physical Activity; Hypertension; Diabetes Mellitus; FHS